PELATIHAN APLIKASI MICROSOFT WORD 2013 PADA SMP H. A. JOHANSYAH. A BANJARMASIN - Yusri Ikhwani; Haldi Budiman; Muhammad Rasyidan (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2015)
Microsoft Word is one of the software / word processing program created by Microsoft and included in bandle Microsoft Office. Microsoft Word into a word processing program that is reliable and most widely used by computer users. So with the Microsoft Word so provide enormous benefits to the world of technology is constantly evolving, in terms of word processors used for productive activities, educational and various other things that require a powerful word processing application.